Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Co-production of low technical readiness level climate science through prototyping with users. Prospects in a European case study - E. Delpiazzo; K. Bülow; E. Baulenas Serra; C. Teichmann; J.H. Christensen; D. Matte; D. Bojovic; P. Kalverla; B.B. B. Booth; C.R. Goddard; F. Fung; B. Solaraju-Murali; et al. (Environmental Science & Policy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

IFN-β as a therapeutic agent for influenza A virus infection in old mice - Wenxin Wu; Jeremy S. Alexander; Yang Song; J. Leland Booth; Alexandra K. Ford; Jordan P. Metcalf; Douglas A. Drevets (GeroScience, 2026)

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

In poor taste: leaf palatability traits are not correlated with aboveground enemy release - Zoe A. Xirocostas; Eve Slavich; Susan E. Everingham; Juha-Pekka Salminen; Louis Booth; Roslyn Gleadow; Jeff Ollerton; Riin Tamme; Begoña Peco; Vincent Lesieur; S. Raghu; Robert R. Junker; et al. (Oecologia, 2026)

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ozone dose-response relationships for wheat can be derived using photosynthetic-based stomatal conductance models - P. Pande; F. Hayes; S. Bland; N. Booth; H. Pleijel; L.D. Emberson (Agricultural and Forest Meteorology, 2024)

Design and calibration of a nitrate decision support tool for groundwater wells in Wisconsin, USA - Paul F. Juckem; Nicholas T. Corson-Dosch; Laura A. Schachter; Christopher T. Green; Kelsie M. Ferin; Eric G. Booth; Christopher J. Kucharik; Brian P. Austin; Leon J. Kauffman (Environmental Modelling & Software, 2024)

Further insights into killer whales Orcinus orca preying on white sharks Carcharodon carcharias in South Africa - A Towner; P Micarelli; D Hurwitz; MJ Smale; AJ Booth; C Stopforth; E Jacobs; FR Reinero; V Ricci; A Di Bari; S Gavazzi; G Carugno; et al. (African Journal of Marine Science, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Exploring contaminants as a disruptor of temperature-dependent sex determination in sea turtle hatchlings - Arthur D. Barraza; Larissa Young; Caitlin E. Smith; David T. Booth; Christine A. Madden Hof; Kimberly A. Finlayson; Frederic D. L. Leusch; Jason P. van de Merwe (Frontiers in Marine Science, 2023)
Sea turtle nesting beaches are experiencing increased sand temperatures as climate change progresses. In one major green turtle ( Chelonia mydas ) nesting beach in the northern Great Barrier Reef, over 99 percent of hatchlings are female. The effects of contaminants on sea turtle hatchling sex determination are not often explored. Liver samples were collected from green turtle hatchlings that were sacrificed for histological sex determination in a parallel study on the effects of sand cooling on sex ratios, and analysed for trace elements via acid digestion and organic contaminants via in vitro cytotoxicity bioassays. Chromium, antimony, barium, and cadmium have previously been demonstrated to be estrogenic, and concentrations of these elements were used to calculate three estrogenic indexes for each clutch: predicted relative estrogenic potency (PEEQA), the sum of percent trace elements above the median of all samples (TEOM), and the sum of percent estrogenic elements above the median of all samples (EstroEOM). Excluding an outlier clutch, cadmium, antimony, and EstroEOM had significant positive relationships with sex ratio deviation. Mean clutch cobalt, lead, antimony and barium, also had a significant positive relationship with clutch sex ratio. There was no relationship between in vitro cytotoxicity of liver extracts and sex ratio, however, 9% of hatchlings had organic contaminants high enough to suggest potential cellular damage. Contaminant effects on sex determination are likely to be caused by a mixture of contaminant interactions as well as temperature. Many trace elements detected in this study have also been linked to negative health effects on hatchlings in previous studies. Considering the risks of feminization due to climate change and potential contaminant effects on hatchling health and sex determination, future studies exploring contaminant effects on sea turtle hatchling sex determination are recommended.

Futures for invasive alien species management: using bottom-up innovations to envision positive systemic change - J. L. van Velden; R. Biggs; T. Hichert; P. Booth; C. Büchner-Marais; K. J. Esler; M. Lewarne; L. J. Potgieter; S. J. Rahlao; A. J. Rebelo; T. B. Robinson; N. J. van Wilgen; et al. (Sustainability Science, 2023)
Invasive alien species (IAS) pose a key threat to biodiversity, the economy and human well-being, and continue to increase in abundance and impact worldwide. Legislation and policy currently dominate the global agenda for IAS, although translation to localised success may be limited. This calls for a wider range of responses to transform IAS management. An under-appreciated strategy to achieve success may come from bottom-up, experimental innovations (so-called “seeds”), which offer alternative visions of what may be possible for IAS management in the future. We present an application of a participatory process that builds on such innovations to create alternative visions of the future, with actionable pathways to guide change. Through a series of workshops with practitioners and academics, we used this process to explore alternative positive futures for IAS management in South Africa. We then identified a set of domains of change, that could enable these visions to be actioned by appropriate stakeholders. The domains of change highlight the social–ecological nature of the IAS sector, with interconnected actions needed in financial, cultural, social, technological and governance spheres. Key domains identified were the need to shift mindsets and values of society regarding IAS, as well as the need for appropriate and functional financing. This participatory futuring process offers a way to interrogate and scale bottom-up innovations, thereby creating optimism and allowing stakeholders to engage constructively with the future. This represents an important step in fostering the potential of bottom-up innovations to transform IAS management.

Foliar Nutrients Reflect Variation in Floristic Quality and Hydrology of Calcareous Fens - Arthur C. Ryzak; David Bart; Eric G. Booth; Steven P. Loheide (Wetlands, 2022)

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Land O’Lakes Workshop on Microsampling: Enabling Broader Adoption - Enaksha R Wickremsinhe; Qin C. Ji; Carol R. Gleason; Melanie Anderson; Brian P. Booth (The AAPS Journal, 2020)

A comparative analysis of genetic hearing loss phenotypes in European/American and Japanese populations - W. Daniel Walls; Hideaki Moteki; Taylor R. Thomas; Shin-ya Nishio; Hidekane Yoshimura; Yoichiro Iwasa; Kathy L. Frees; Carla J. Nishimura; Hela Azaiez; Kevin T. Booth; Robert J. Marini; Diana L. Kolbe; et al. (Human Genetics, 2020)

Current Perspectives on Ligand-Binding Assay Practices in the Quantification of Circulating Therapeutic Proteins for Biosimilar Biological Product Development - T. M. Thway; Y. M. Wang; B. P. Booth; K. Maxfield; S. M. Huang; I. Zineh (The AAPS Journal, 2020)

Determining contemporary and historical sediment sources in a large drainage basin impacted by cumulative effects: the regulated Nechako River, British Columbia, Canada - David Gateuille; Philip N. Owens; Ellen L. Petticrew; Barry P. Booth; Todd D. French; Stephen J. Déry (Journal of Soils and Sediments, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Stress analysis of NW Jordan: New episode of tectonic rejuvenation related to the Dead Sea transform fault - M. Alawabdeh; J. V. Pérez-Peña; J. M. Azañón; G. Booth-Rea; A. M. Abed; M. Atallah; J. P. Galve (Arabian Journal of Geosciences, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Fish assemblages associated with oil industry structures on the continental shelf of north‐western Australia - N. Pradella; A. M. Fowler; D. J. Booth; P. I. Macreadie (Journal of Fish Biology, 2014)
This study provides the first assessment of fish associations with oil and gas structures located in deep water (85–175 m) on Australia's north‐west continental shelf, using rare oil industry video footage obtained from remotely operated vehicles. A diverse range of taxa were observed associating with the structures, including reef‐dependent species and transient pelagic species. Ten commercially fished species were observed, the most abundant of which was Lutjanus argentimaculatus , with an estimated biomass for the two deepest structures (Goodwyn and Echo) of 109 kg.

Meeting Report: Metabolites in Safety Testing (MIST) Symposium—Safety Assessment of Human Metabolites: What’s REALLY Necessary to Ascertain Exposure Coverage in Safety Tests? - Hongying Gao; Abigail Jacobs; Ronald E. White; Brian P. Booth; R. Scott Obach (The AAPS Journal, 2013)

Ecological niche modeling of the invasive potential of Nile tilapia Oreochromis niloticus in African river systems: concerns and implications for the conservation of indigenous congenerics - Tsungai A. Zengeya; Mark P. Robertson; Anthony J. Booth; Christian T. Chimimba (Biological Invasions, 2013)

EEFIT mission to Haiti following the 12th January 2010 earthquake - S. P. G. Madabhushi; K. Saito; E. D. Booth (Bulletin of Earthquake Engineering, 2013)

Linaria dalmatica invades south-facing slopes and less grazed areas in grazing-tolerant mixed-grass prairie - Dana M. Blumenthal; Andrew P. Norton; Samuel E. Cox; Erik M. Hardy; Glen E. Liston; Lisa Kennaway; D. Terrance Booth; Justin D. Derner (Biological Invasions, 2012)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Precipitation extremes and the impacts of climate change on stormwater infrastructure in Washington State - Eric A. Rosenberg; Patrick W. Keys; Derek B. Booth; David Hartley; Jeff Burkey; Anne C. Steinemann; Dennis P. Lettenmaier (Climatic Change, 2010)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Home range of an estuarine‐dependent fish species Pomadasys commersonnii in a South African estuary - A.‐R. CHILDS; A. J. BOOTH; P. D. COWLEY; W. M. POTTS; T. F. NÆSJE; E. B. THORSTAD; F. ØKLAND (Fisheries Management and Ecology, 2008)
The home range and area use of spotted grunter, Pomadasys commersonnii (Haemulidae) (Lacepède), were investigated in the Great Fish estuary, South Africa. Forty individuals (263–698 mm TL) were surgically implanted with acoustic‐coded transmitters and manually tracked during two periods in 2003. Tagged fish spent on average 68 and 77% of the time in the estuary and the remaining time at sea during the two periods, respectively. While in the estuary, there was large variation in home range size, home range length and the number of home range areas amongst individuals. Larger fish had larger home ranges and more core areas than smaller fish. The home ranges of 29 individuals (74%) occurred in the lower reaches of the estuary, suggesting that the proclamation of a no‐take zone in this high use area could benefit this over‐exploited estuarine fishery species.

Reduced physical activity and risk of chronic disease: the biology behind the consequences - Frank W. Booth; Matthew J. Laye; Simon J. Lees; R. Scott Rector; John P. Thyfault (European Journal of Applied Physiology, 2008)

Measuring degradation of zinc phosphide residues in possum stomach contents - L. E. Brown; P. Fisher; G. Wright; L. Booth (Bulletin of Environmental Contamination and Toxicology, 2007)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

Ratio-dependent response of a temperate Australian estuarine system to sustained nitrogen loading - Melanie J. Bishop; Brendan P. Kelaher; Marcus P. Lincoln Smith; Paul H. York; David J. Booth (Oecologia, 2006)

Gene expression and genotyping studies implicate the interleukin 7 receptor in the pathogenesis of primary progressive multiple sclerosis - D. R. Booth; A. T. Arthur; S. M. Teutsch; C. Bye; J. Rubio; P. J. Armati; J. D. Pollard; R. N. S. Heard; G. J. Stewart (Journal of Molecular Medicine, 2005)

Impact of pharmacometrics on drug approval and labeling decisions: A survey of 42 new drug applications - Venkatesh A. Bhattaram; Brian P. Booth; Roshni P. Ramchandani; B. Nhi Beasley; Yaning Wang; Veneeta Tandon; John Z. Duan; Raman K. Baweja; Patrick J. Marroum; Ramana S. Uppoor; Nam Atiqur Rahman; Chandrahas G. Sahajwalla; et al. (The AAPS Journal, 2005)

Sensing and adapting to acid stress - Ian R. Booth; P. Cash; C. O'Byrne (Antonie van Leeuwenhoek, 2002)

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

Groundwater geochemistry in shallow aquifers above longwall mines in Illinois, USA - C. J. Booth; L. P. Bertsch (Hydrogeology Journal, 1999)

Effects of solvent on DNA adduct formation in skin and lung of CD1 mice exposed cutaneously to benzo(a)pyrene - Ewan D. Booth; Robert W. Loose; William P. Watson (Archives of Toxicology, 1999)

Development of a carcinogenic potency index for dermal exposure to viscous oil products - Henk C. A. Brandt; Ewan D. Booth; Paul C. de Groot; William P. Watson (Archives of Toxicology, 1999)

Studies on the dermal and systemic bioavailability of polycyclic aromatic compounds in high viscosity oil products - David Potter; Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; Robert A. J. Priston; Alan S. Wright; William P. Watson (Archives of Toxicology, 1999)

Methylglyoxal production in bacteria: suicide or survival? - G. P. Ferguson; S. Tötemeyer; M. J. MacLean; I. R. Booth (Archives of Microbiology, 1998)

Correlation of 32 P-postlabelling-detection of DNA adducts in mouse skin in vivo with the polycyclic aromatic compound content and mutagenicity in Salmonella typhimurium of a range of oil products - Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; William P. Watson (Archives of Toxicology, 1998)

Introgression of quantitative trait loci (QTLs) determining stripe rust resistance in barley: an example of marker-assisted line development - T. Toojinda; E. Baird; A. Booth; L. Broers; P. Hayes; W. Powell; W. Thomas; H. Vivar; G. Young (Theoretical and Applied Genetics, 1998)

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)

An agro-economic assessment of seed-potato storage technologies in the Philippines - Michael J. Potts; W. V. D. Albert; Felix R. Rutab; Elmo O. Sano; Pepito P. Mariano; Robert H. Booth (American Journal of Potato Research, 1983)